HIV Prevention 2020: a framework for delivery and a call for action. Issue 7 (July 2016) - Dehne, Karl L; Dallabetta, Gina; Wilson, David; Garnett, Geoff P; Laga, Marie; Benomar, Elizabeth; Fakoya, Ade; Baggaley, Rachel C; Nelson, Lisa J; Kasedde, Susan; Bermejo, Alvaro; Warren, Mitchell; et al.
Summary: Although effective programmes are available and several countries have seen substantial declines in new HIV infections, progress in the reduction of adult HIV incidence has been slower than expected worldwide and many countries have not had large decreases in new infections in adults despite large reductions in paediatric infections. Reasons for slow progress include inadequate commitment, investment, focus, scale, and quality of implementation of prevention and treatment interventions. The UNAIDS–Lancet Commission on Defeating AIDS—Advancing Global Health reported that the provision of large-scale, effective HIV prevention programmes has failed and called on stakeholders to "get serious about HIV prevention". An ambitious worldwide target has been set by UNAIDS to reduce new infections below 500 000 by 2020—a 75% reduction from 2010. Models show that such a reduction requires a combination of primary prevention interventions and preventative effects of treatment. Achievement of the target will require more effective delivery of HIV prevention for sufficient coverage in populations at greatest risk of infection ensuring that interventions that have proved effective are made available, barriers to their uptake are overcome, demand is created, and use is consistent and occurs at the right scale with high coverage. This paper discusses how programmatic targets for prevention in a worldwide plan could be used to re-energise the HIV prevention approach. A management framework is proposed outlining global, regional, national, and subnational actions and is summarised in a call for action on HIV prevention for 2020.